Características histomorfométricas do intestino delgado de fetos suínos - Junqueira, Marseile Reis (2015)
In this study aimed to evaluate fetuses’ weight influence from primiparous on development of swine intestinal mucosa in different gestational periods (50, 80 and 106 days). Fetuses from 15 females were used, five for each gestational period in a completely randomized design in which fetuses from each gestational period were divided into four different classes, depending on the weight, featuring four treatments (C1, C2, C3, C4). Each fetus constituted one experimental unit. The average weight were: at 50 days: C1 34.90 g; C2 40.07 g; C3 46.91 g; C4 50.81 g/; at 80 days: C1 281.71 g; C2 380.94 g; C3 423.81 g; C4 509.29 g/ and at 106 days: C1 919.64 g; C2 1090.36 g; C3 1214.36 g; C4 1380.86 g. After slaughter and reproductive tract removal the fetuses were weighed and longitudinally open for duodenum and jejunum collection. For morphometry analysis and area were used the Axion Vision v4.8 and ImageJ v1.46 programs, respectively. Thus, it was observed that at 50 days the C1 presented a lower duodenal area (P<0.05). In the same period the jejunum area was higher in fetuses of C4. At 80 days fetuses of C1 and C4 had the lowest and the highest duodenal area, respectively (P<0.05) while the jejunum had larger area C3 and C4 (P<0.05). At 106 days, the jejunum area is larger at the C2 and C3 in relation to C1 and only in C3 the absorptive surface is better compared to C1 (P<0.05). At 50 days the smallest and the largest width of duodenal crypt are in C1 and C2, respectively. At 80 days it is observed difference only in duodenum, being C1 crypt depth greater than C2 (P<0.05). At 106 days crypt depth is greater in C1 and smaller in C2, being the lowest C2 relation and greater C1 (P<0.05). In the jejunum greater villus height was observed in C3 and lower heights in C1 and C4 (P<0.05), there was a greater villous/crypt ratio in C2 and smaller in C1 and C4 (P<0.05). Thus, it can be concluded that fetal weight influences the intestinal development, there are, in certain gestational stages, correlation between weight and the analyzed variables. So, a low fetal weight can affect the intestinal mucosa development.